Assessment of the teaching staff in Health Sciences - Rosa María Fenoll-Brunet (Universitat Politècnica de València, 2021)
Health science teachers are essential to ensure the health of the population and the continuously updated training of health professionals. However, in some countries, clinical teaching staff individually assume teaching responsibility based on their professional competence, without there being a regulated pedagogical training for clinical teachers, specific and recognized into the professional career of the health professions.This manuscript summarizes the educational context of the health professions and describes the challenges commonly faced by health sciences teachers. What teaching skills should they have? How do health professionals become teachers? How can be assessed faculty development in the health sciences? How can be promoted innovation and excellence in medical, dental and veterinary education? Sharing experiences and existing models at the international level could be useful to benchmark how some countries have implemented and recognize the professional teaching trajectory of their health professionals, how they comprehensively regulate the teaching of health sciences throughout life, from basic to postgraduate training and continuous professional development. The objective of this manuscript is to provide a comprehensive vision of teaching in the field of health sciences, some reflections and a selection of references of interest. "Health is one of the world's challenges; therefore the training of teachers in health sciences should be considered a priority for any country"